Parental Education About Stigma And Discrimination In Cleft Lips And Palate Patient: Community Empowerment - Ruby Riana Asparini; Feby Alfina Damayanti; Erina Sofia Atha; Revi Ruli Pranita; Shabrina Adilia Roida (DokTIn MEDIKA Jurnal Pengabdian Masyarakat, 2022)
Background: Cleft lip and palate (CLP) is the second most common congenital craniofacial anomaly, with 1 in 600 births worldwide. Children with CLP are very vulnerable to stigma and discrimination. Purpose: Changes in parents' understanding of the stigmatization and discrimination experienced by families with children born with CLP.Methods: This was a cross-sectional descriptive study among parents of children born with CLP. Education about stigmatization and discrimination is given.Pre-test and post-test are also performed using an interviewer-administered questionnaire.The total score was analyzedusing paired t-test. Results: The total score of parents' education on stigma and discrimination in CLP was initially 8.29 and increased to 9.39 after receiving education. The change in knowledge was statistically significant (p = 0.029). Conclusion: The education provided has been shown to have a positive impact on parents' understanding of the stigmatization and discrimination experienced by families with children born with CLP.